2006
DOI: 10.1016/j.ijdevneu.2005.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid pretreatment prevents the reduction of Na+,K+‐ATPase and butyrylcholinesterase activities in rats subjected to acute hyperhomocysteinemia

Abstract: The main objective of the present study was to evaluate the effect of folic acid pretreatment on parietal cortex Na(+),K(+)-ATPase and serum butyrylcholinesterase activities in rats subjected to acute hyperhomocysteinemia. Animals were pretreated daily with an intraperitoneal injection of folic acid (5 mg/kg) or saline from the 22th to the 28th day of age. Twelve hours after the last injection of folic acid or saline, the rats received a single subcutaneous injection of homocysteine (0.6 micromol/g of weight b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…In this situation, GLAST and GLT‐1, which are dependent of sodium‐gradient, could reverse the direction of glutamate transport, resulting in accumulation of extracellular glutamate (Danbolt, 2001; Maragakis and Rothstein, 2004; Sheldon and Robinson, 2007; Nicholls, 2008). Consistent with these findings, we previous showed that Hcy chronic and acute administrations inhibited Na + , K + ‐ATPase activity in plasmatic membranes prepared from parietal cortex of rats (Matté et al, 2004, 2006, 2007), as well as in hippocampus (Streck et al, 2002; Wyse et al, 2002). Contributing with this hypothesis, a similar effect has been reported for ischemia (Rossi et al, 2000; Camacho and Massieu, 2006; Sheldon and Robinson, 2007), and some neurodegenerative diseases (Greenamyre et al, 1999; Higgins et al, 1999), that have been related to hyperhomocysteinemia (Mattson et al, 2002; Obeid et al, 2007).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In this situation, GLAST and GLT‐1, which are dependent of sodium‐gradient, could reverse the direction of glutamate transport, resulting in accumulation of extracellular glutamate (Danbolt, 2001; Maragakis and Rothstein, 2004; Sheldon and Robinson, 2007; Nicholls, 2008). Consistent with these findings, we previous showed that Hcy chronic and acute administrations inhibited Na + , K + ‐ATPase activity in plasmatic membranes prepared from parietal cortex of rats (Matté et al, 2004, 2006, 2007), as well as in hippocampus (Streck et al, 2002; Wyse et al, 2002). Contributing with this hypothesis, a similar effect has been reported for ischemia (Rossi et al, 2000; Camacho and Massieu, 2006; Sheldon and Robinson, 2007), and some neurodegenerative diseases (Greenamyre et al, 1999; Higgins et al, 1999), that have been related to hyperhomocysteinemia (Mattson et al, 2002; Obeid et al, 2007).…”
Section: Discussionsupporting
confidence: 71%
“…We also evaluated the immunocontent of GLAST and GLT‐1 in parietal cortex of rats subjected to chronic hyperhomocysteinemia. Parietal cortex was selected because patients presenting hyperhomocysteinemia exhibit cortical atrophy (Sachdev, 2005), moreover we have shown that Hcy elicits several neurotoxic effects in this cerebral structure (Matté et al, 2006, 2007, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Data were statistically analyzed by one-way ANOVA. Representative immunological reactions are shown alterations caused by Hcy (Matte et al 2006;Stefanello et al 2005;Tagliari et al 2006), we also tested whether the effect of Hcy on the formation of filopodia in C6-glioma cells could be prevented by these compounds. Cells were treated with folic acid (5 lM), trolox (80 lM), and ascorbic acid (1 mM) in the absence (controls) or presence of 100 or 500 lM Hcy for 4 h. We observed that they totally prevented the 100 lM Hcy-induced filopodia formation, since the number of cells containing abundant and long filopodia attained levels similar to controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that folic acid supplementation can significantly reduce the risk of these disorders [614]. Folates are the key cofactors in one-carbon metabolism.…”
Section: Introductionmentioning
confidence: 99%